EVALUATION OF THE CURRENT PRACTICE OF DELIVERING INTRAVENOUS OPIOIDS INFUSIONS IN A UK PAEDIATRIC HOSPITAL. Issue 9 (17th August 2016) - Rashed, Asia N; Tomlin, Stephen
Abstract : Introduction: Opiate intravenous infusions are the therapy of choice in severe pain. However, administering infusions to children requires complex dosage calculations, rate adjustments and often multiple manipulations of injectable medicines to obtain the final "ready to use" solution for both continuous infusion and additional boluses; potentially putting children at high risk.1 2 Aim: To investigate the practice and accuracy of healthcare professionals (HCPs) in hospital theatres and wards in preparing morphine infusions for nurse/patient controlled analgesia (N/PCA) use in a UK children's hospital. Methods: A mixed methods study in which direct observation of HCPs preparing paediatric morphine infusions for N/PCA in theatres and on wards, focus groups with HCPs and quantitative analysis of morphine concentration in the syringe using UV-Vis Spectrophotometer. The British Pharmacopoeia (BP) reference limits of ±7.5% were used to compare label strength (LS) of morphine infusion with measured concentration. Results: The preparation of 153 syringes was observed which related to 128 paediatric patients [mean age (±sd) 7.5 years±5.6; 65.3% male]. 64% (98/153) were prepared by anaesthetists in theatres, 36% (55/153) by nurses at ward level. Major differences in preparation methods were identified. The final volume prepared was above the required volume (50 mL) in 35.9% (55/153) preparations. Wearing gloves during preparation was not followed in theatre for 83.7% (82/98) of syringes. No decontamination of morphine ampoules was undertaken during preparation of any syringe. Inconsistency in the appropriate syringe size used to withdraw drug from the ampoule was observed in both theatres and wards. Lack of appreciation of the overage in morphine ampoules by HCPs was identified. Of the syringes analysed 61.5% (48/78) had a concentration outside the BP reference limits (92.5–107.5% of LS), most were in excess (83.3%, 40/48). Of these 20.8% (10/48) deviated by more than +20%, with one deviated by 100%. Conclusion: This study identified that variation in preparation techniques followed by HCPs may result in morphine N/PCA dosages that are significantly higher or lower than that prescribed. Also, lack of understanding of ampoule overage, accuracy of the syringe size used and the ability to measure small volumes led to inaccurate concentrations in prepared infusions.